An Aptitude for Altitude: Are Epigenomic Processes Involved? - Julian, Colleen G. (Frontiers in Physiology, 2019)
In recent years, high-throughput genomic technologies and computational advancements have invigorated efforts to identify the molecular mechanisms regulating human adaptation to the chronic hypoxia of high altitude. Although exceptional progress has been achieved with respect to the identification of genomic regions showing evidence of recent positive selection, many of the key ‘hypoxia tolerant' phenotypes of highland populations have not yet been linked to putative adaptive genetic variants. As a result, fundamental questions regarding the biological processes by which such adaptations are acquired remain unanswered. This Mini Review discusses the hypothesis that the epigenome works in coordination with underlying genomic sequence to govern human adaptation to high altitude by influencing adaptive capacity and phenotypic variability under conditions of environmental hypoxia. Efforts to understand the complex interactions between the genome, epigenome, and environment are essential to more fully appreciate the mechanisms underlying human adaptation to hypoxia, clarify its implications for biomedical research and explore how evolutionary processes influence disease susceptibility.